The importance of charged aerosols in the polar mesosphere in connection with Noctilucent Clouds and Polar Mesosphere Summer Echoes - Blix, Tom Arild (The Antarctic and Arctic Middle Atmospheres: Their Differences and Similarities, 1999)
A number of campaigns have been conducted in order to study Polar Mesosphere Summer Echos (PMSE) and Noctilucent Clouds (NLC) in the period 1991–1994. Several sounding rockets have been launched through these layers with measurements being performed on upleg as well as downleg. These include measurements of positive ions and electrons in both ram and wake positions, as well as measurements of charged aerosols in ram on upleg. In this paper we will review these measurements and make a preliminary classification of the data based upon the presence of PMSE and/or NLC. One of the mechanisms responsible for PMSE is the presence of neutral air turbulence in combination with a high Schmidt number. We will briefly discuss this type of echo using in situ rocket data. Differences and similarities of PMSE and NLC as observed both in the Arctic and the Antarctic will be discussed. Observations show that especially PMSE are much more frequent in the Arctic. This may be due to a difference in the water vapour content or the temperature at mesopause heights. Lack of data in the Antarctic makes it difficult to decide which of these two factors are the most important. More measurements, especially co-ordinated in situ and ground-based lidar and radar measurements, are needed to discuss the Arctic and Antarctic similarities and differences in further detail.
Keywords: Antarktis; astrofysikk; atmosfæren; geofysikk; mesosfæren; meteorologi; polarområdene

In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

A global model tool for three-dimensional multiyear stratospheric chemistry simulations: Model description and first results - Rummukainen, Markku; Isaksen, Ivar S A; Rognerud, Bjørg; Stordal, Frode (Journal of Geophysical Research: Atmospheres, 1999)
The paper presents a new global modeling tool, Stratospheric Chemical Transport Model 2. It has been developed for effective three-dimensional multiyear stratospheric chemistry studies, featuring an extensive chemistry scheme, heterogeneous processing on sulfate aerosols, and some polar stratospheric cloud processes. The transport algorithm maintains sub-grid-scale distributions and connects vertically the stratospheric layers, even in a coarse vertical grid. The model has been integrated for 49 months, recycling 1 year of precalculated transport from a middle atmosphere general circulation model. One year of daily National Centers for Environmental Prediction global analyses are used as temperatures. Diurnal cycles of photolysis rates are recalculated every 7 days to give interaction with ozone changes. The model is able to describe most of the geographical and seasonal ozone variability and the meridional distributions of ozone, reactive nitrogen, chlorine, and bromine. Stratospheric diurnal cycles for nitrogen, hydrogen, chlorine, and bromine species are captured in detail. The upper stratosphere ozone deficiency, typical to models, is large. Its sensitivity to different ways of tuning are explored. Midlatitude, rather than polar, wintertime processes have so far been the focus in this model tool. The present transport and grid resolution are not suited for realistic simulations at high latitudes. As there is only a limited inclusion of polar stratospheric cloud (PSC) microphysics, chemical processing in the cold polar lower stratosphere also cannot be well simulated. For example, the Antarctic ozone hole is not simulated, but the modeled chemistry should be suitable for warm Arctic winters when type II PSCs and particle sedimentation do not occur.
Keywords: Antarktis; geofysikk; meteorologi; ozonlaget; polarområdene; stratosfæren; stratosfærisk kjemi

Climatic trend and the retreat and disintegration of ice shelves on the Antarctic Peninsula: an overview - Skvarca, Pedro; Rack, Wolfgang; Rott, Helmut; Ibarzábal Donángelo, Teresa (Polar Research, 1999)
Observation of the retreat and disintegration of ice shelves around the Antarctic Peninsula during the last three decades and associated changes in air temperature, measured at various meteorological stations on the Antarctic Peninsula, are reviewed. The climatically induced retreat of the northern Larsen Ice Shelf on the east coast and of the Wordie, George VI, and Wilkins ice shelves on the west coast amounted to about 10 000 km2 since the mid-1960s. A summary is presented on the recession history of the Larsen Ice Shelf and on the collapse of those sections north of Robertson Island in early 1995. The area changes were derived from images of various satellites, dating back to a late 1963 image from the recently declassified US Argon space missions. This photograph reveals a previously unknown, minor advance of the northern Larsen Ice Shelf before 1975. During the period of retreat a consistent and pronounced warming trend was observed at the stations on both east and west coasts of the Antarctic Peninsula, but a major cause of the fast retreat and final collapse of the northernmost sections of the Larsen Ice Shelf were several unusually warm summers. Temperature records from the nearby station Marambio show that a positive mean summer temperature was reached for the first time in 1992-93. Recent observations indicate that the process of ice shelf disintegration is proceeding further south on both sides of the Antarctic Peninsula.
Keywords: Antarktis; brehylle; glasiologi; isbrem; isshelf; klimaendringer; meteorologi; satellittbilder

Sixty year 10Be record from Greenland and Antarctica - Aldahan, A.; Possnert, G.; Johnsen, S. J.; Clausen, H. B.; Isaksson, Elisabeth; Karlen, W.; Hansson, M. (Proceedings of the Indian Academy of Sciences - Earth and Planetary Sciences, 1998)
We report in this study the distribution of 10Be in the top 40 m of the Renland ice core (East Greenland) and in a 30 m long core from DML (Dronning Maud Land, Antarctica) for the period 1931–1988. The two sites show differences in10Be content, the Antarctica site showing smaller variance and a lower average 10Be annual flux. Similarly, the average accumulation rate (cm water equivalent year−1) is higher in the Renland relative to DML. The variability in accumulation (precipitation) rates seems to explain part of the difference in10Be flux between the two polar sites. Cyclic fluctuations of 10Be flux correlate with the 11-year sunspot number and cosmic ray intensity than with the aa index (perturbation of the geomagnetic activity by the solar wind). Our data corroborate 10Be cyclic fluctuation pattern from the Dye 3 ice core and confirm a promising potential for correlation of global and local events.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi; meteorologi; polarområdene

Ambient air levels and atmospheric long-range transport of persistent organochlorines to Signy Island, Antarctica - Kallenborn, Roland; Oehme, Michael; Wynn-Williams, David D; Schlabach, Martin; Harris, Joyce (Science of The Total Environment, 1998)
Levels of persistent organic pollutants (POPs), such as polychlorinated biphenyls and pesticides have been determined in ambient air at Signy Island, Antarctica, over a period of 17 weeks. Mean concentrations for single polychlorinated biphenyls (0.02–17 pg/m3), for chlordanes (0.04–0.9 pg/m3), DDT compounds (0.07–0.40 pg/m3) and γ-hexachlorocyclohexane (HCH, 22 pg/m3) were comparable to those in Arctic air. However, α-HCH levels were approximately one order of magnitude lower. Compared to the Arctic, differences were also observed in the concentration ratios of α-/γ-HCH and chlordane compounds. Two possible atmospheric long-range transport episodes from South America were found by comparing 10-day back trajectories with observed concentration changes. The lower limits of determination (LOD) were mainly governed by the field blanks. They were satisfactory for the most volatile PCBs. However, many concentrations for DDT and chlordane compounds were below the LODs (range 0.1–1 pg/m3) or even the instrumental detection limit (0.01–0.03 pg/m3).
Keywords: Antarktis; atmosfæren; forurensning; langtransport; luftforurensning; meteorologi; miljøgifter; polarområdene

A Comparison of the CCM3 Model Climate Using Diagnosed and Predicted Condensate Parameterizations - Rasch, Philip J.; Kristjánsson, Jón Egill (Journal of Climate, 1998)
A parameterization is introduced for the prediction of cloud water in the National Center for Atmospheric Research Community Climate Model version 3 (CCM3). The new parameterization makes a much closer connection between the meteorological processes that determine condensate formation and the condensate amount. The parameterization removes some constraints from the simulation by allowing a substantially wider range of variation in condensate amount than in the standard CCM3 and tying the condensate amount to local physical processes. The parameterization also allows cloud drops to form prior to the onset of grid-box saturation and can require a significant length of time to convert condensate to a precipitable form, or to remove the condensate. The free parameters of the scheme were adjusted to provide reasonable agreement with top of atmosphere and surface fluxes of energy. The parameterization was evaluated by a comparison with satellite and in situ measures of liquid and ice cloud amounts. The effect of the parameterization on the model simulation was then examined by comparing long model simulations to a similar run with the standard CCM and through comparison with climatologies based upon meteorological observations. Global ice and liquid water burdens are higher in the revised model than in the control simulation, with an accompanying increase in height of the center of mass of cloud water. Zonal averages of cloud water contents were 20%–50% lower near the surface and much higher above. The range of variation of cloud water contents is much broader in the new parameterization but was still not as large as measurements suggest. Differences in the simulation were generally small. The largest significant changes found to the simulation were seen in polar regions (winter in the Arctic and all seasons in the Antarctic). The new parameterization significantly changes the Northern Hemisphere winter distribution of cloud water and improves the simulation of temperature and cloud amount there. Small changes were introduced in the cloud fraction to improve consistency of the meteorological parameterizations and to attempt to alleviate problems in the model (in particular, in the marine stratocumulus regime). The small changes did not make any appreciable improvement to the model simulation. The new parameterization adds significantly to the flexibility in the model and the scope of problems that can be addressed. Such a scheme is needed for a reasonable treatment of scavenging of atmospheric trace constituents, and cloud aqueous or surface chemistry. The addition of a more realistic condensate parameterization provides opportunities for a closer connection between radiative properties of the clouds, and their formation and dissipation. These processes must be treated for many problems of interest today (e.g., anthropogenic aerosol–climate interactions).
Keywords: Antarktis; klimamodeller; klimatologi; meteorologi; polarområdene

The semi-annual oscillation and Antarctic climate. Part 1: influence on near surface temperatures (1957–79) - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
We studied the influence of the semi-annual oscillation (SAO) on near-surface temperatures in Antarctica, using observations of 27 stations that were operational during (part of) the period 1957–79. For the annual cycle of surface pressure, the second harmonic explains 17–36% of the total variance on the Antarctic Plateau, 36–68% along the East Antarctic coast and almost 80% on the west coast of the Peninsula, and decreases further to the north. As a result of the amplification of the wave-3 structure of the circulation around Antarctica, a significant modification of the seasonal cooling is observed at many stations. The magnitude of this modification is largely determined by the strength of the temperature inversion at the surface: the percentage of the variance explained by the second harmonic of the annual temperature cycle is then largest on the Antarctic Plateau (11–18%), followed by the large ice shelves and coastal East Antarctica (6–12%) and stations at or close to the Peninsula (0–5%). A significant coupling between the half-yearly wave in surface pressure and that in surface temperature is found for coastal East Antarctica, which can be directly explained by the changes in meridional circulation brought about by the SAO. We show that the coupling of Antarctic temperatures to the meridional circulation is not only valid on the seasonal time scale of the SAO, but probably also on daily and interannual time scales. This has important implications for the interpretation of time series of Antarctic temperatures, a problem that will be addressed in part 2 of this paper.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

The semi-annual oscillation and Antarctic climate. Part 2: recent changes - Van Den Broeke, Michiel R. (Antarctic Science, 1998)
Following a weakening of the semi-annual oscillation (SAO) since the mid-1970s, the half-yearly pressure wave in the Southern Hemisphere has become less significant. As a result, May/June temperatures have decreased in East Antarctica, which has moderated Antarctic warming. Spectral analysis of 87 years of pressure data at Orcadas suggest that the recent weakening of the SAO is part of the natural variability of the Southern Hemisphere circulation on decadal timescales. We interpret the time series of composite Antarctic temperature in terms of the historical strengthening and weakening of the SAO. If the dominant oscillations that occurred in the past prove to be persistent, an accelerated East Antarctic warming trend is expected for the coming decades. There are indications that the strength of the SAO is linked to the Southern Oscillation, in the sense that warm phases of the Southern Oscillation coincide with strong westerlies, a weakly developed SAO and below-average temperatures in East Antarctica. Temperatures on the west coast of the Antarctic Peninsula show strongly deviant patterns, which can not be explained by the same mechanism that applies to East Antarctica.
Keywords: Antarktis; fysisk geografi; klimatologi; meteorologi

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Representation of Antarctic Katabatic Winds in a High-Resolution GCM and a Note on Their Climate Sensitivity - Broeke, Michiel R. van den; Wal, Roderik S. W. van de; Wild, Martin (Journal of Climate, 1997)
Keywords: Antarktis; Dronning Maud Land; glasiologi; klimatologi; meteorologi

Spatial and temporal variation of sublimation on Antarctica: Results of a high-resolution general circulation model - van den Broeke, Michiel R. (Journal of Geophysical Research: Atmospheres, 1997)
In this paper we use output of a high-resolution general circulation model (ECHAM-3 T106, resolution 1.1°?1.1°) to study the spatial and temporal variation of sublimation on Antarctica. First, we compare model results with available observations of sublimation rates. The yearly cycle, with small latent heat fluxes during the winter, is well reproduced, and the agreement with sparsely available spot observations is fair. The model results suggest that a significant 10?15% of the annual precipitation over Antarctica is lost through sublimation and that sublimation plays an important role in the formation of blue ice areas. A preliminary analysis of the atmospheric boundary layer moisture budget shows that the spatial variation of sublimation in the coastal zone of East Antarctica can be explained by variations of horizontal advection of dry air. Dry air advection, and thus surface sublimation, is enhanced in areas where katabatic winds are strong and have a large downslope component and where the Antarctic topography drops suddenly from the plateau to the coastal zone. In areas where horizontal advection is small, like the plateau and the large ice shelves, special conditions must be met to make significant sublimation at the surface possible.
Keywords: Antarktis; atmosfæren; geofysikk; meteorologi

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Studies and monitoring of climate-sensitive melt areas in Jutulgryta - Winther, Jan-Gunnar; Liston, Glen E; Bruland, Oddbjørn; Elvehøy, Hallgeir; Sand, Knut (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; hydrologi; klima; meteorologi

Report of the Norwegian Antarctic Research Expedition 1989/90 - Norsk, Polarinstitutt (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; Dronning Maud Land; NARE 1989/90; Troll forskningsstasjon; Weddellhavet; geologi; marin økologi; meteorologi; zoologi

Glaciological and meteorological measurements in Dronning Maud Land - Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1989/90, 1990)
Keywords: Dronning Maud Land; NARE 1989/90; ekspedisjoner; forskning; glasiologi; meteorologi